2021
DOI: 10.1002/jmri.27626
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pancreatic Fibrosis Grading by Multiparametric Quantitative Magnetic Resonance Imaging

Abstract: Background: Early detection and grading of pancreatic fibrosis (PF) are important and challenging clinical goals. Purpose: To determine main pancreatic duct (MPD) diameter, pancreatic thickness, and grades of PF via magnetic resonance elastography (MRE), T1 mapping, and intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI), assessing respective diagnostic performances. Study Type: Prospective. Subjects: Histopathologic and imaging records (MRE, T1 mapping, and IVIM-DWI) generated by 144 patients b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(59 citation statements)
references
References 33 publications
3
56
0
Order By: Relevance
“…Some studies reported correlation of the T1 SIR specifically with pancreatic exocrine dysfunction measured by the endoscopic pancreatic function tests [ 21 , 28 ]. We identified three publications that correlated histopathology on surgical specimens with MRI parenchymal features (T1 SIR, T1 relaxation time, diffusion-weighted imaging, and MR elastography) [ 26 , 30 , 31 ]. These studies found a significant correlation of MRI parenchymal findings with the degree of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported correlation of the T1 SIR specifically with pancreatic exocrine dysfunction measured by the endoscopic pancreatic function tests [ 21 , 28 ]. We identified three publications that correlated histopathology on surgical specimens with MRI parenchymal features (T1 SIR, T1 relaxation time, diffusion-weighted imaging, and MR elastography) [ 26 , 30 , 31 ]. These studies found a significant correlation of MRI parenchymal findings with the degree of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…[47] Zhao et al [44] found that 68 Ga-FAPI PET/CT showed a greater number of peritoneal metastases in the mesentery and omentum than 18 F-FDG (Fig. 2), even though both 68 Ga-FAPI and 18 F-FDG scans show similarly increased uptake in the primary pancreatic cancer. [44,50] Even a small size of peritoneal carcinomatosis can be detected on 68 Ga-FAPI.…”
Section: Primary Cancermentioning
confidence: 96%
“…[37,59] 68 Ga-FAPI presents lower physiological uptake than 18 F-FDG in normal tissues, including brain parenchyma, myocardium, blood pool, liver, spleen, kidney cortex, and normal pancreatic tissue. Furthermore, the gastrointestinal tract shows almost no 68 Ga-FAPI uptake compared with 18 F-FDG. Published studies have demonstrated no significant biodistribution differences between a variety of FAP radioligands.…”
Section: Primary Cancermentioning
confidence: 98%
“…Early detection of fibrotic changes in the pancreatic parenchyma could potentially help to prevent more severe morphologic disruption and fibrosis progression. Unfortunately, while functional examinations of the pancreas are rarely used in a clinical setup and often not reliable and reproducible, pancreatic biopsies are invasive with possible for complications and demand high‐grade technical skill, making it unpractical for routine evaluation of PF 3 …”
mentioning
confidence: 99%
“…Unfortunately, while functional examinations of the pancreas are rarely used in a clinical setup and often not reliable and reproducible, pancreatic biopsies are invasive with possible for complications and demand high-grade technical skill, making it unpractical for routine evaluation of PF. 3 Improvement in pancreatic magnetic resonance (MR) image quality and resolution has recently been achieved with reduced field of view techniques. 4 The reduction of the typical pancreatic imaging artifacts due to bowel air and motion allows for reliable application of multiparametric MR imaging to different pancreatic diseases and quantification of pancreatic fat and fibrous tissue with T2*-corrected Dixon technique and intravoxel incoherent motion model (IVIM) diffusion-weighted imaging (DWI).…”
mentioning
confidence: 99%